4-Dimensional printing: exploring current and future capabilities in biomedical and healthcare systems—a Concise review - Agarwal, Neha; Solanki, Vijendra Singh; Ameta, Keshav Lalit; Yadav, Virendra Kumar; Gupta, Premlata; Wanale, Shivraj Gangadhar; Shrivastava, Ruchi; Soni, Anjali; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Bioengineering and Biotechnology, 2023)
4-Dimensional Printing (4DP) is the latest concept in the pharmacy and biomedical segment with enormous potential in dosage from personalization and medication designing, which adopts time as the fourth dimension, giving printed structures the flexibility to modify their morphology. It can be defined as the fabrication in morphology with the help of smart/intelligent materials like polymers that permit the final object to alter its properties, shape, or function in response to external stimuli such as heat, light, pH, and moisture. The applications of 4DP in biomedicines and healthcare are explored with a focus on tissue engineering, artificial organs, drug delivery, pharmaceutical and biomedical field, etc. In the medical treatments and pharmaceutical field 4DP is paving the way with unlimited potential applications; however, its mainstream use in healthcare and medical treatments is highly dependent on future developments and thorough research findings. Therefore, previous innovations with smart materials are likely to act as precursors of 4DP in many industries. This review highlights the most recent applications of 4DP technology and smart materials in biomedical and healthcare fields which can show a better perspective of 4DP applications in the future. However, in view of the existing limitations, major challenges of this technology must be addressed along with some suggestions for future research. We believe that the application of proper regulatory constraints with 4DP technology would pave the way for the next technological revolution in the biomedical and healthcare sectors.